Attentional Differences as a Function of Rock Climbing Performance - Garrido-Palomino, Inmaculada; Fryer, Simon; Giles, Dave; González-Rosa, Javier J.; España-Romero, Vanesa (Frontiers in Psychology, 2020)
The purpose of this study was to investigate the relationship between attention (using two different attention task) and self-reported climbing ability whilst considering potential confounding factors [sex, age, climbing experience and cardiorespiratory fitness (CRF)] in a group of experienced climbers. Accuracy of response (AC) and reaction time (RT) from two different attention tasks using the Vienna Test System, along with self-reported on-sight and red-point climbing ability, were assessed in thirty-five climbers. Linear regression revealed that climbers with the highest self-reported on-sight grade had better AC during the attention task. Linear regression models revealed, after controlling for potential confounders, that AC, measured using two attention tasks, was positively related to climbers’ highest self-reported on-sight climbing ability (β: 0.388; p: 0.031). No significant differences were found between AC and self-reported red-point climbing ability (β: 0.286; p: 0.064). No significant relationship was found between RT and climbing ability (β: -0.102 to 0.020; p: 0.064). In conclusion, higher level rock climbers appear to have an enhanced attention which is related to on-sight lead climbing style, and thus it may be an important component of climbing performance. Coaches should consider incorporating techniques to train attention based on on-sight climbing style in climbers.